HOW CAN SHARIA COOPERATIVES ALLEVIATE POVERTY IN ACEH? - Khairil Umuri; Eddy Gunawan; Syahriyal Syahriyal; Hendra Halim (universitas teuku umar, 2025)
Sharia cooperatives have emerged as an alternative solution in poverty alleviation efforts, especially in Aceh Province, which has officially implemented a Sharia-based financial system. This study aims to explore the role of Sharia cooperatives in empowering impoverished communities through a qualitative descriptive approach informed by a literature review. Based on a review of more than 25 national and international academic sources, this study highlights how sharia cooperatives provide inclusive financial access, create employment opportunities, and promote economic independence, particularly for vulnerable groups, including women and Micro And Small Enterprises (MSMEs). The findings demonstrate that sharia cooperatives not only enhance economic welfare but also foster social solidarity, expand access to decent housing, and integrate Islamic values into community life. In addition, sharia cooperatives also support the achievement of the Sustainable Development Goals (SDGs), especially in the aspects of poverty alleviation (SDG 1) and women's empowerment (SDG 5). Despite facing structural challenges such as low managerial capacity and regulatory support, sharia cooperatives still have great potential as a value-based economic instrument in realizing a just and prosperous society. This study recommends integrating sharia cooperatives into the national digital-based economic ecosystem to strengthen their contribution to inclusive and equitable development.